The Benefits of High Relaxivity for Brain Tumor Imaging: Results of a Multicenter Intraindividual Crossover Comparison of Gadobenate Dimeglumine with Gadoterate Meglumine (The BENEFIT Study) - Vaneckova, M.; Herman, M.; Smith, M.P.; Mechl, M.; Maravilla, K.R.; Weichet, J.; Spampinato, M.V.; Žižka, J.; Wippold, F.J.; Baima, J.J.; Babbel, R.; Bültmann, E.; et al. (American Journal of Neuroradiology, 2015)
BACKGROUND AND PURPOSE: Gadobenate dimeglumine (MultiHance) has higher r1 relaxivity than gadoterate meglumine (Dotarem) which may permit the use of lower doses for MR imaging applications. Our aim was to compare 0.1- and 0.05-mmol/kg body weight gadobenate with 0.1-mmol/kg body weight gadoterate for MR imaging assessment of brain tumors.MATERIALS AND METHODS: We performed crossover, intraindividual comparison of 0.1-mmol/kg gadobenate with 0.1-mmol/kg gadoterate (Arm 1) and 0.05-mmol/kg gadobenate with 0.1-mmol/kg gadoterate (Arm 2). Adult patients with suspected or known brain tumors were randomized to Arm 1 (70 patients) or Arm 2 (107 patients) and underwent 2 identical examinations at 1.5T. The agents were injected in randomized-sequence order, and the 2 examinations were separated by 2–14 days. MR imaging scanners, imaging sequences (T1-weighted spin-echo and T1-weighted high-resolution gradient-echo), and acquisition timing were identical for the 2 examinations. Three blinded readers evaluated images for diagnostic information (degree of definition of lesion extent, lesion border delineation, visualization of lesion internal morphology, contrast enhancement) and quantitatively for percentage lesion enhancement and lesion-to-background ratio. Safety assessments were performed.RESULTS: In Arm 1, a highly significant superiority (P < .002) of 0.1-mmol/kg gadobenate was demonstrated by all readers for all end points. In Arm 2, no significant differences (P > .1) were observed for any reader and any end point, with the exception of percentage enhancement for reader 2 (P < .05) in favor of 0.05-mmol/kg gadobenate. Study agent–related adverse events were reported by 2/169 (1.2%) patients after gadobenate and by 5/175 (2.9%) patients after gadoterate.CONCLUSIONS: Significantly superior morphologic information and contrast enhancement are demonstrated on brain MR imaging with 0.1-mmol/kg gadobenate compared with 0.1-mmol/kg gadoterate. No meaningful differences were recorded between 0.05-mmol/kg gadobenate and 0.1-mmol/kg gadoterate.GBCAgadolinium-based contrast agentLBRlesion-to-background ratioSIsignal intensityT1GRET1-weighted high resolution gradient-echoT1SET1-weighted spin-echo